Post-Ischemic Inflammation in the Brain - Yoshimura, Akihiko; Shichita, Takashi (Frontiers in Immunology, 2012)
Post-ischemic inflammation is an essential step in the progression of brain ischemia-reperfusion injury. In this review, we focus on the post-ischemic inflammation triggered by infiltrating immune cells, macrophages, and T lymphocytes. Brain ischemia is a sterile organ, but injury-induced inflammation is mostly dependent on Toll-like receptor (TLR) 2 and TLR4. Some endogenous TLR ligands, high mobility group box 1 (HMGB1) and peroxiredoxin family proteins, in particular, are implicated in the activation and inflammatory cytokine expression in infiltrating macrophages. Following macrophage activation, T lymphocytes infiltrate the ischemic brain and regulate the delayed phase inflammation. IL-17-producing γδT lymphocytes induced by IL-23 from macrophages promote ischemic brain injury, whereas regulatory T lymphocytes suppress the function of inflammatory mediators. A deeper understanding of the inflammatory mechanisms of infiltrating immune cells may lead to the development of novel neuroprotective therapies.